Atypical function of a centrosomal module in WNT signalling drives contextual cancer cell motility - Yi Luo (Nature Portfolio, 2019)
Centrosomes function in cell migration by organizing microtubules. Here, Luo et al. surprisingly show that centrosome proteins also control migration after recruitment by Wnt-PCP proteins to the cell cortex, leading to actin remodelling and protrusive activity relevant to aggressive cancer motility.